Trädans betydelse i odlingssystemen och dess effekter på näringsutlakning - Falk, Hanna (SLU/Dept. of Soil and Environment, 2017)
For more than 10 000 years ago man turned from being a hunter to conduct agriculture. Agriculture has since then developed and from the Stone Age until today four different crop cultivation systems can be distinguished; slash and burn farming, agricultural mower, agricultural crop rotation and agricultural industry. The fallow in agriculture was introduced around the younger Iron Age. Bare fallow, green fallow and stubble fallow are common fallow in today's agriculture. Of all arable land in Sweden, 6.5 percent was fallow in 2016. The green fallow, especially perennial green fallow with flowers, is good for biodiversity. A green fallow also has a low nitrogen leakage compared to bare fallow. The bare fallow can have twice as high nitrogen leakage than grain cultivation. Nitrogen leakage is for example influenced by soil and tillage. When the roots of the plants are cut down after harvesting the organically bound nitrogen is mineralized. Inorganic nitrogen can easily be leached from the ground if vegetation is missing. Biodiversity and reduced nitrogen leakage are important for a sustainable agriculture. Therefore, green fallow could be applied next to the field or on grain farms instead of ley field.